Trends in Serious Infections in Rheumatoid Arthritis - Mhuircheartaigh, Orla Ni (2013)
OBJECTIVE: To examine trends in the rates of serious infections among patients diagnosed with rheumatoid arthritis (RA) in 1995-2007 compared to rates previously reported from the same geographical area diagnosed in 1955-1994. METHODS: A population-based inception cohort of patients with RA in 1995-2007 was assembled and followed through their complete medical records until death, migration, or December 31, 2008. All serious infections (requiring hospitalization or IV antibiotics) were recorded. Person-year (py) methods were used to compare rates of infection. RESULTS: Among 464 patients with incident RA in 1995-2007, 54 had ≥1 serious infection (178 total). These were compared to609 patients with incident RA in 1955-1994 (290 experienced ≥1 serious infection; 740 total). The rate of serious infections declined from 9.6 per 100py in the 1955-1994 cohort to 6.6 per 100py in the 1995-2007 cohort. However, serious gastrointestinal infection rates increased from 0.5 per 100py in the 1955-1994 cohort to 1.25 per 100py in the 1995-2007 cohort. Among patients with a history of serious infection, the rate of subsequent infection increased from 16.5 per 100py in 1955-1994 to 37.4 per 100py in 1995-2007. There was an increase in the rate of serious infections in patients who received biologic agents, but this did not reach significance. CONCLUSIONS: Aside from gastrointestinal infections, the rate of serious infections in patients with RA has declined in recent years. However, the rate of subsequent infections was higher in recent years than previously reported.